Autophagy Protects the Blood-Brain Barrier Through Regulating the Dynamic of Claudin-5 in Short-Term Starvation - Yang, Zhenguo; Huang, Chunnian; Wu, Yongfu; Chen, Bing; Zhang, Wenqing; Zhang, Jingjing (Frontiers in Physiology, 2019)
The blood-brain barrier (BBB) is essential for the exchange of nutrient and ions to maintain the homeostasis of central nervous system (CNS). BBB dysfunction is commonly associated with the disruption of endothelial tight junctions and excess permeability, which results in various CNS diseases. Therefore, to maintain the function of BBB is crucial to prevent or treat CNS disorders. Here, we show that serum starvation disrupted the function of endothelial barrier as evidenced by decreased trans-endothelial resistance, increased permeability, and redistribution of tight junction proteins such as Claudin-5 (Cldn5). Further analyses revealed that autophagy was activated and protected the integrity of endothelial barrier by scavenging ROS and inhibiting the redistribution of Cldn5 under starvation, as evidenced by accumulation of autophagic vacuoles and increased expression of LC3II/I, ATG5 and Lamp1. In addition, autophagosome was observed to package and eliminate the delocalized and cytosolic Cldn5 as detected by immunoelectron microscopy (IEM) and stimulated emission depletion (STED) microscope. Moreover, AKT/mTOR pathway was verified to be involved in the protective autophagy induced by starvation. Our data demonstrated that autophagy played an essential role in maintaining the integrity of endothelial barrier by regulating the localization of Cldn5 under starvation.